2022
DOI: 10.1038/s41598-022-19482-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the impact of wall structure on the thermal performance of double-channel porous solar wall

Abstract: With the improvement of people’s living standards, they have higher requirements for indoor thermal comfort in the cold season. Solar wall utilizing solar energy for heating can reduce carbon emissions and achieve carbon neutrality. In the aspect of solar wall research, the influence of wall structure on the thermal performance of double-channel porous solar wall is limitedly investigated. In fact, the optimization design of wall structure is important for the thermal performance of solar wall and its applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Also, the water tank temperature reached 40 • C in summer. Qi et al [18] numerically investigated the effect of wall structure on the effectiveness of a two-channeled SW with a porous surface. They found that the temperature of a porous wall is constantly greater than the temperature of the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the water tank temperature reached 40 • C in summer. Qi et al [18] numerically investigated the effect of wall structure on the effectiveness of a two-channeled SW with a porous surface. They found that the temperature of a porous wall is constantly greater than the temperature of the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%